Analyzing Effectiveness of Development Aid Projects: Evaluation Ratings or Project Indicators? - Laura Metzger; Isabel Günther (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2013)
Ongoing empirical research on the drivers of project-aid effectiveness relies on World Bank evaluation ratings across heterogeneous aid sectors. This leads to two problems. First, it is difficult to identify which dimension of project performance World Bank evaluation ratings are measuring precisely. Second, only project management variables, which are sector independent, can be included in the analysis. This study concentrating on an analysis of 150 water supply projects enables us to work with a more precise and objective performance measure by defining sector-specific indicators of improved water supply. Moreover, we are able to analyze the impact of project design in addition to project management. We find that evaluation ratings and indicators of improved water supply are positively but weakly correlated. Project management variables have a higher impact on evaluation ratings whereas project design variables have a higher impact on improving water supply to the target group. Various independent variables even change sign if indicators of improved water supply instead of evaluation ratings are chosen as a performance measure of project-aid effectiveness. Taking into account project design in addition to project management and country characteristics considerably increases the share of variation in project performance that can be explained.
Keywords: F35; O19; 330; Aid effectiveness; evaluation; indicators; water supply